Efektivitas Tata Kelola Kolaboratif Multi Sektor dalam Percepatan Penurunan Stunting di Kabupaten Bone - Anisa Fitri; Sulmiah; Nina Agustina; Widyawati; Dewi Sulfa Saguni (PT. Palem Edukasi Nusantara, 2025)
This study aims to analyze the effectiveness of multi-sector collaborative governance in accelerating stunting reduction in Bone Regency. This research departs from the still high prevalence of stunting which has an impact on the quality of human resources and regional economic productivity. The research approach used is qualitative descriptive with data collection techniques through interviews, observations, and documentation of stakeholders. Data analysis uses the Miles, Huberman, and Saldana models through the stages of reduction, presentation, and drawing conclusions. The results of the study show that cross-sector collaboration in reducing stunting in Bone Regency has been quite effective from the five dimensions of collaboration effectiveness according to Roberts (2016), namely common goals, mutuality, enabling environment, trust, and certain personal characteristics. This collaboration has contributed to reducing the prevalence of stunting from 25.3% in 2023 to 21.9% in 2024 based on e-PPGBM data. The conclusion of this study confirms that adaptive and evidence-based collaborative governance is effective in accelerating the achievement of stunting reduction targets in Bone Regency.